1981
DOI: 10.1063/1.328771
|View full text |Cite
|
Sign up to set email alerts
|

Interface states and electron spin resonance centers in thermally oxidized (111) and (100) silicon wafers

Abstract: Interface states and electron spin resonance centers have been observed and compared in thermally oxidized (111) and (100) silicon wafers subjected to various processing treatments. The ESR Pb signal, previously assigned to interface ⋅Si≡Si3 defects on (111) wafers, was found to have two components on (100): an ⋅Si≡Si3 center oriented in accord with (100) face structure, and an unidentified center consistent with ⋅Si≡Si2O. The quantitative proportionality of Pb spin concentration to midgap interface trap densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
166
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 552 publications
(177 citation statements)
references
References 11 publications
9
166
0
2
Order By: Relevance
“…One of the peaks has a g-factor of 2.0002 which is close to the reported value (g = 2.0005) of deep hole oxide trap E' defects [38]. The other peak has a g-factor of 2.0058 which is intermediate between the g-values reported for P b0 (g 1 = 2.0015 -parallel to (111); g 2 = 2.0080; g 3 = 2.0087 -parallel to (011)) and P b1 (g 1 = 2.0012; g 2 = 2.0076 -parallel to (111); g 3 = 2.0052 -parallel to (011)) at the orientation used in the experiment [32,38]. We have labeled this the P b0 defect since this is the most-commonly observed defect peak in EDMR.…”
Section: B Optical Selection Of Spin-pair Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the peaks has a g-factor of 2.0002 which is close to the reported value (g = 2.0005) of deep hole oxide trap E' defects [38]. The other peak has a g-factor of 2.0058 which is intermediate between the g-values reported for P b0 (g 1 = 2.0015 -parallel to (111); g 2 = 2.0080; g 3 = 2.0087 -parallel to (011)) and P b1 (g 1 = 2.0012; g 2 = 2.0076 -parallel to (111); g 3 = 2.0052 -parallel to (011)) at the orientation used in the experiment [32,38]. We have labeled this the P b0 defect since this is the most-commonly observed defect peak in EDMR.…”
Section: B Optical Selection Of Spin-pair Speciesmentioning
confidence: 99%
“…While the SDR mechanism for phosphorus donors is believed to primarily be mediated by mid-gap danglingbond P b0 defects [18,26,32,33], previous EDMR measurements have measured E' defects [30] as well as P b1 defects and a central donor pair resonance [26]. It was recently shown that EDMR in Si:P is primarily sensitive to those donors located within roughly the first 20 nm of the Si/SiO 2 surface [34].…”
Section: Spin Dependent Recombinationmentioning
confidence: 99%
“…P b centers are trivalent Si atoms at the c-Si/SiO 2 interface. They dominate interface trapping and recombination, they are paramagnetic when uncharged [15,16] and they are strongly localized, anisotropic electronic states [17]. For the c-Si (111) surface orientation, all P b centers point into a direction perpendicular to the interface.…”
Section: A Pedmr Experiments With P B -Centersmentioning
confidence: 99%
“…The broader peak at B 0 = 347.1 mT is an unresolved superposition of signal contributions from P b0 centers that have different orientations with respect to the Si (100) surface, which results in resonances at g = 2.0039 and g = 2.0081 for the orientation of the sample with respect to the magnetic field orientation indicated in Fig. 1(c) [17,18]. The current transients at the three resonances exhibit identical dynamics: An initial strong photocurrent decrease caused by the higher singlet content followed by a slower increase of the current originating from the quenching of the number of triplet states which also have a finite recombination probability [20].…”
mentioning
confidence: 99%
“…In order to probe 31 P donor electron spins, spindependent excess charge carrier recombination through so-called P b0 centers is used. P b0 centers are trivalent Si atoms at the interface between crystalline silicon (c-Si) and silicon dioxide (SiO 2 ) that introduce localized, paramagnetic states in the Si band gap and dominate electron trapping and recombination at the interface [17,18]. If a neutral P b0 center is located in the vicinity of a 31 P donor, the electron bound to the 31 P and the electron in the P b0 center can form a coupled spin pair [19,20], whose wave function |Ψ can exist in an arbitrary superposition of any of its four energy eigenstates.…”
mentioning
confidence: 99%